Characterization of eight polymorphic microsatellite DNA markers and mitochondrial cytochrome c oxidase subunit II gene in Bali myna Leucopsar rothschildi. Issue 1 (4th August 2020) - Ogata, M.; Ishii, H.; Onuma, M.
Abstract : The aim of this study was to develop polymorphic DNA markers for Bali myna Leucopsar rothschildi . The mitochondrial cytochrome c oxidase subunit II (COII) gene was sequenced, and polymorphic microsatellite loci were searched using Next Generation Sequencing. Three haplotypes of mitochondrial COII gene were found in a Japanese population of Bali myna in human care. Eight polymorphic microsatellite DNA markers were also identified. In a sample group of 22 individuals, numbers of alleles and expected heterozygosities of the eight microsatellite loci ranged from two to three and 0·241 to 0·609, respectively. These results suggested that the genetic variation of this species might be low, similar to that of other threatened bird species. Abstract : The aim of this study was to develop polymorphic DNA markers for Bali myna Leucopsar rothschildi . The mitochondrial cytochrome c oxidase subunit II (COII) gene was sequenced, and polymorphic microsatellite loci were searched using Next Generation Sequencing. Three haplotypes of mitochondrial COII gene were found in a Japanese population of Bali myna in human care. Eight polymorphic microsatellite DNA markers were also identified. These results suggested that the genetic variation of this species might be low, similar to that of other threatened bird species. (Photo: Toshio Shiraishi, Preservation and Research Center, Yokohama)